Transcriptome Analysis of a Bloom-Forming Cyanobacterium Microcystis aeruginosa during Ma-LMM01 Phage Infection - Morimoto, Daichi; Kimura, Shigeko; Sako, Yoshihiko; Yoshida, Takashi (Frontiers in Microbiology, 2018)
Microcystis aeruginosa forms massive blooms in eutrophic freshwaters, where it is constantly exposed to lytic cyanophages. Unlike other marine cyanobacteria, M. aeruginosa possess remarkably abundant and diverse potential antiviral defense genes. Interestingly, T4-like cyanophage Ma-LMM01, which is the sole cultured lytic cyanophage infecting M. aeruginosa, lacks the host-derived genes involved in maintaining host photosynthesis and directing host metabolism that are abundant in other marine cyanophages. Based on genomic comparisons with closely related cyanobacteria and their phages, Ma-LMM01 is predicted to employ a novel infection program that differs from that of other marine cyanophages. Here, we used RNA-seq technology and in silico analysis to examine transcriptional dynamics during Ma-LMM01 infection to reveal host transcriptional responses to phage infection, and to elucidate the infection program used by Ma-LMM01 to avoid the highly abundant host defense systems. Phage-derived reads increased only slightly at 1 h post-infection, but significantly increased from 16% of total cellular reads at 3 h post-infection to 33% of all reads by 6 h post-infection. Strikingly, almost none of the host genes (0.17%) showed a significant change in expression during infection. However, like other lytic dsDNA phages, including marine cyanophages, phage gene dynamics revealed three expression classes: early (host-takeover), middle (replication), and late (virion morphogenesis). The early genes were concentrated in a single ~5.8-kb window spanning 10 open reading frames (gp054–gp063) on the phage genome. None of the early genes showed homology to the early genes of other T4-like phages, including known marine cyanophages. Bacterial RNA polymerase (σ70) recognition sequences were also found in the upstream region of middle and late genes, whereas phage-specific motifs were not found. Our findings suggest that unlike other known T4-like phages, Ma-LMM01 achieves three sequential gene expression patterns with no change in host promoter activity. This type of infection that does not cause significant change in host transcriptional levels may be advantageous in allowing Ma-LMM01 to escape host defense systems while maintaining host photosynthesis.